Global Warming Affects the Pathogenesis of Important Fish Diseases in European Aquaculture - George Rigos; Francesc Padrós; Maria Constenla; Ana Jerončić; Dimitra Kogiannou; Sofia Consuegra; Mikolaj Adamek; Ivona Mladineo (Reviews in Aquaculture, 2026)
Global warming remains a neglected environmental challenge for the sustainability of primary production, particularly aquaculture, which is highly susceptible to the spread of established pathogens and the induction of emerging infectious diseases under warming conditions. Over the past decade, Europe has experienced dramatically high temperatures that may impact both farmed fish and their pathogens in a largely unpredictable manner. While, in general, warming may boost the rate of disease transmission and its virulence by increasing pathogens' fitness in weakened hosts, some diseases characteristic of cooler environments may become rare. Field data is still largely fragmented, but in vitro experiments reveal that almost 28 microbial diseases in European finfish farming could be facilitated by climate warming. Innovative mitigation tools, such as fish selective breeding, epigenetic programming, the development of new vaccines, and alternative treatments, may prove essential in coping with the effects of rising water temperatures on fish diseases in Europe.